Prioritising target behaviours for research in diabetes: Using the nominal group technique to achieve consensus from key stakeholders - Mc Sharry, Jennifer (Res Involv Engagem, 2016)
PLAIN ENGLISH SUMMARY: The behaviour of people with diabetes (e.g. taking medication) and the behaviour of doctors and other healthcare professionals (e.g. checking patients’ blood sugar) are important. Our research group wanted to select one patient behaviour and one healthcare professional behaviour as topics to research in Ireland. Patients and healthcare professionals are not usually asked to help decide on research topics. In this study, we wanted to bring together patients, healthcare professionals and policy makers to help us decide on the most important target behaviours for research in diabetes in Ireland. We worked with 24 participants, including people with diabetes, diabetes healthcare professionals and policy makers. First, participants suggested behaviours they thought were important to target for research in diabetes. Participants then attended a meeting and ranked which of the behaviours were the most important and discussed the results of the rankings as a group. We identified the most highly ranked patient and healthcare professional behaviours. The top ranked behaviour for people with Type 1 diabetes was to ‘take insulin as required’ and for people with Type 2 diabetes was to ‘attend and engage with structured education programmes’. ‘Engage in collaborative goal setting with patients’ was the top ranked behaviour for healthcare professionals. Our study shows it is possible for researchers to work with people with diabetes, healthcare professionals and policy makers to decide on research topics. The top ranked behaviours will now be researched by our group in Ireland. ABSTRACT: Background Working with patients, healthcare providers, and policy makers to prioritise research topics may enhance the relevance of research and increase the likelihood of translating research findings into practice. The aim of the present study was to work with key stakeholders to identify, and achieve consensus on, the most important target behaviours for research in diabetes in Ireland. Methods Twenty-four participants, including people with diabetes, diabetes healthcare professionals and policy makers, took part in a nominal group technique consensus process. Through an online survey, participants generated lists of important target behaviours in three areas: managing Type 1 diabetes, managing Type 2 diabetes and preventing Type 2 diabetes. Participants then attended a research prioritisation meeting and ranked target behaviours in two rounds, with group discussion between ranking rounds. For each of the three key areas, the six top ranked behaviours relevant to people with diabetes and healthcare professionals were identified. Results In most cases, the most highly ranked behaviour was the same for Ranking 1 and Ranking 2 and consensus increased in relation to endorsement of top ranked behaviours. However, some behaviours did change position between rankings. The top behaviour relevant to people with Type 1 diabetes was ‘taking insulin as required’ and for people with Type 2 diabetes was ‘attending and engaging with structured education programmes’. ‘Engage in collaborative goal setting with patients’ was the top ranked behaviour relevant to healthcare professionals for managing both Type 1 and Type 2 diabetes. For preventing Type 2 diabetes, 'engage in healthy behaviours as a family' was the highest ranked population behaviour and ‘attend and engage with behaviour change training’ was the highest ranked professional behaviour. Conclusions It is possible to work with a diverse group of stakeholders to inform the diabetes research agenda. The priorities identified were co-produced by key stakeholders, including patients, healthcare professionals and policy makers, and will inform the development of a programme of behavioural research in diabetes in Ireland. The study also provides a worked example of a research prioritisation process using the nominal group technique, and identified limitations, which may be useful for other researchers.